Power generation process control system fault detection method - LIANG YU; CAI YUAN; LIU HONGYAN; WANG SHILIN; FANG LIANHANG; NIU YUGUANG (2016)
The present invention discloses a power generation process control system fault detection method, which comprises the steps of: carrying out matrix factorization on a training matrix X after noise reduction and standardization processing by adopting a principal component analysis PCA method, and adopting a score matrix T as an initial value W0 of a base matrix W; carrying out iteration solution on the base matrix W and a weight coefficient matrix H of the training matrix X by adopting an alternating least square method with nonnegative constrains; constructing a monitoring statistics Tn and SPEn based on nonnegative matrix factorization, calculating probability density functions PDF of the monitoring statistics Tn and SPEn separately by utilizing a kernel density estimation method, setting a significance level and solving control limits of the monitoring statistics Tn and SPEn separately; and calculating to obtain an approximate value W-hat test of a base matrix of a test matrix Xtest by utilizing the weight